PENGARUH KINERIA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Simanihuruk, Peran (Jurnal Manajemen dan Bisnis, 2011)
Indonesia country has a comparative advantage in producing oil, so the master sizeable international market for many commodities such as cocoa, rubber, tea, coï¬‚ee, pepper, vanilla, copra, crude palm oil, essential oils, tobacco and areca nut. In 2008, the stock price of the entire plantation companies listed on the Indonesia Stock Exchange (IDX) down. In 2009, there is one company that its stock price fell, while in 2010 there were two companies that share price fell. So the research problem is: "Is the ï¬nancial performance (current ratio, debt ratio, total asset turnover, and return on equity) have a signiï¬cant effect on the stock prices of plantation companies listed on the Stock Exchange?". The research hypothesis is "ï¬nancial performance (current ratio, debt ratio, total asset turnover, and return on equity) have a signiï¬cant eï¬ct on the stock prices of plantation companies listed on the Stock Exchange". This study aims to identify and analyze the effect of the ï¬nancial performance of the stock price on the plantation company listed on the Stock Exchange. Beneï¬ts of the research is to add insight and knowledge of the author about the impact the ï¬nancial performance of the stock price. Population were all plantation companies listed on the Stock Exchange in 2007 - 2010 by 7 companies. This population as well as sample. Data collected through the techniques required documentation. The data analysis technique used is multiple linear regression. From the analysis, it was concluded that the value of 12.5314-4 Fhitung with probability 0.000015, so H0 is rejected. That is, ï¬nancial performance (current ratio, debt ratio, total asset turnover, and return on equity) to simultaneously have a signiï¬cant ejfect on stock prices on the plantation company listed on the Stock Exchange, may be accepted at a signiï¬cance level of 5 percent. judging from the t test, it was concluded that the current ratio, total asset turnover, and return on equity signiï¬cantly partial to the stock price. the debt ratio is partially signiï¬cant eï¬‚%ct on stock prices, can be accepted at a signiï¬cance level of5 percent. The diversity of the dependent variable, ie stock prices can be explained by a variety of independent variables, namely ï¬nancial performance (current ratio, debt ratio, total asset turnover and return on equity) of 68.5473 per cent, while 31.4527 percent is explained by other factors. Judging from the regression coeï¬‚icient values, it is known that thecurrent ratio, total asset turnover and return on equity have a positive ejfect on stock prices. Iudging from the regression coeï¬‚icient values, it is known that the debt ratio negatively aï¬ect the stock price. Iudgingfrorn the regression coeï¬‚icient values, it is known that the debt ratio contributed most to the stock price. Advice given consi. on to the investors and other researchers are better, investors or prospective investors to consider th rent ratio, debt ratio, total asset turnover and return on equity ï¬rms in investing in plantation companies listed on the Stock Exchange, making proï¬table investment decisions made .